Media, communication and the struggle for social progress. (August 2018) - Couldry, Nick; Rodriguez, Clemencia; Bolin, Göran; Cohen, Julie; Volkmer, Ingrid; Goggin, Gerard; Kraidy, Marwan; Iwabuchi, Koichi; Qiu, Jack Linchuan; Wasserman, Herman; Zhao, Yuezhi; Rincón, Omar; et al.
This article discusses the role of media and communications in contributing to social progress, as elaborated in a landmark international project – the International Panel on Social Progress. First, it analyses how media and digital platforms have contributed to global inequality by examining media access and infrastructure across world regions. Second, it looks at media governance and the different mechanisms of corporatized control over media platforms, algorithms and content. Third, the article examines how the democratization of media is a key element in the struggle for social justice. It argues that effective media access – in terms of distribution of media resources, even relations between spaces of connection and the design and operation of spaces that foster dialogue, free speech and respectful cultural exchange – is a core component of social progress.